Animal and Pandemic Influenza : A Framework for Sustaining Momentum, Fifth Global Progress Report July 2010 - UN System Influenza Coordination; World Bank (New York: United Nations, 2014)
Global efforts continue to work towards ensuring a world capable of preventing, detecting, and responding to animal and public health risks attributable to zoonoses and animal diseases. Drawing on achievements and experiences of the past five years, the fifth global progress report was produced to support the discussions and to provide a record of key outcomes from international ministerial conference on animal and pandemic influenza (IMCAPI). This report presents a framework for sustaining momentum which was agreed by delegates at the April 2010 IMCAPI. The framework offers three streams of work that need sustained attention by national, regional, and global authorities despite the inevitable waning of public interest in pandemic-related issues. The three work streams are: (a) prevention and control of highly pathogenic avian influenza (HPAI), (b) adoption of one health approaches, and (c) readiness for response to influenza pandemics. For each, the framework envisages two expected outcomes and identifies the actions which contribute to these expected outcomes. It identifies the incentives and institutional arrangements needed to sustain momentum, highlights systems for monitoring progress, and spells out investment priorities particularly to support institutions and systems in the least developed countries. To realize these goals, policy makers are moving away from tackling avian and pandemic influenza through emergency projects or special initiatives. Instead they aim for longer term capacity building through pursuit of effective strategies within existing programs, and the mainstreaming of pandemic readiness skills. The right incentives to achieve this transformation need to be identified and used backed with strategic political and financial support, novel institutional arrangements, and easily applied monitoring systems.